Analysis of regional financial independence, potential for growth, and health services: A case study of regencies/cities in South Sulawesi - Azwar Iskandar (Badan Pemeriksa Keuangan Republik Indonesia, 2021)
This study aims to analyze: (1) the financial independence and commitment of health services in the region; (2) the potential for growth in supporting health services in the region; and (3) the relationship pattern between financial independence and regional potential for growth to achieve the goal of fulfilling health service commitments in the region. This research is explanatory research using a quantitative approach. The results show that: (1) the average level of financial independence of regencies/cities in South Sulawesi Province fall under the high category and relatively independent in terms of source and allocation of regional budgets; (2) the average growth of all regencies/cities in South Sulawesi Province shows positive figures which implies that the prospect of their economic growth has accelerated along with several problems in each regency/city; (3) some regencies/cities with large APBD do not have an increased allocation of resources for health expenditure. On the contrary, some regencies/cities that fall under the category of low budget and financial independence have a better commitment to health service and expenditure. In addition, almost all regencies/cities categorized as having good potential for growth ended up having low performance in health expenditure. The local government has carried out fiscal decentralization, which is defined as the freedom for regions in carrying out policies related to budget politics in the region. Notwithstanding the preceding, the role of the central government is still greatly expected to advocate for the improvement of health expenditure quality.